A Laser Link From Lunar Surface Employing Line-of-Sight MIMO - Schwarz, Robert T.; Giggenbach, Dirk; Knopp, Marcus T.; Knopp, Andreas (Frontiers in Space Technologies, 2021)
Future exploration of our planetary system relies on the Moon as a base and stepping stone to other planets. A high-rate data connection to this celestial body is, therefore, imperative. Free-space optical (FSO) communications will enable continuous broadband connectivity to Earth. Currently pursued concepts incorporate data relay satellites orbiting the Moon, where each individual satellite terminal has to overcome the lunar distance facing restraints on telescope apertures and on beam pointing and tracking accuracies. We propose a concept of one dedicated link originating from a robotic telescope station installed on the lunar surface. We study the conceptual architecture of such an FSO ground node at the lunar surface with a spotlight on the link design at the physical layer. In particular, we increase the FSO channel capacity through multiple transmission- and receiving-apertures. Our findings encourage the application of the Line-of-Sight (LOS) multiple-input multiple-output (MIMO) technology to FSO communications at large link distances typically coming along with space missions, as thereby the maximum MIMO capacity can be achieved. Directing our study on the link geometry such connections seem technically feasible at relatively low system complexity with the receivers located at a single site and the transmitters only few meters apart.